2010
DOI: 10.1247/csf.10004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DAF1/CD55, a Novel Definitive Endoderm Marker

Abstract: ABSTRACT. Although there are several markers available for the identification of endoderm derivatives such as the lung, pancreas, liver, and intestine, there are still very few surface markers available for the prospective isolation of the definitive endoderm. Among these, CXCR4 has been used in combination with E-cadherin as a cell surface marker to identify the definitive endoderm. However, CXCR4 expression decreases in late gut epithelium. Here we report a gene, Decay Accelerating Factor (DAF1/CD55), as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…Decay accelerating factor (DAF1/CD55), a gene found to be highly expressed in ES cell-derived DE, was detected in the DE and mesoderm in early embryos at E8.5 [49]. Flow cytometry analysis of ES cell-derived differentiated cells revealed that DAF1+ cells also expressed CXCR4 on the cell surface.…”
Section: Identification Of De-specific Genes In Es Cell-differentiationmentioning
confidence: 99%
“…Decay accelerating factor (DAF1/CD55), a gene found to be highly expressed in ES cell-derived DE, was detected in the DE and mesoderm in early embryos at E8.5 [49]. Flow cytometry analysis of ES cell-derived differentiated cells revealed that DAF1+ cells also expressed CXCR4 on the cell surface.…”
Section: Identification Of De-specific Genes In Es Cell-differentiationmentioning
confidence: 99%
“…Moreover, we found that Decay Accelerating Factor (DAF1/CD55) as a candidate surface marker for the identification of the early and late definitive endoderm [34]. These results strongly suggest that M15 differentiation system is useful to analyze early developmental steps in vitro.…”
Section: The Mesonephric Cell Line M15 Can Induce the Mouse Es Or Imentioning
confidence: 64%
“…cells are shown to mark the definitive population [32,33]. We recently identified a novel definitive endoderm marker CD55/DAF1 [34], which expression was maintained in more matured endoderm cells.…”
Section: Lineage Specific Generation Of the Definitive Endoderm Cellsmentioning
confidence: 99%
“…However, Cxcr4 expression decreases during development, making the isolation of late definitive endoderm cells difficult. The combination of E-cadherin with CD55 has circumvented this problem by identifying early and late definitive endoderm cells in the embryo, and in ESC-derived cell cultures where GFP is expressed under the promoter of Pdx1 (Shiraki, Harada et al 2010). Our group has also observed the presence of E-cadherin + CD55 + cells in our ESC-IPC cultures ( Figure 4B).…”
Section: Definitive Endoderm Progenitorsmentioning
confidence: 79%
“…In mice, putative definitive endodermal cells that co-express E-cadherin and Decay Accelerating Factor (DAF1/CD55) cell surface markers also express Pdx1 (Shiraki, Harada et al 2010). Discoidin domain receptor tyrosine kinase 1 (DDR1) and delta/notch-like EGF related receptor (DNER) have been also indicated as possible murine pancreatic progenitor surface markers with bioinformatics studies confirmed by immunohistochemistry (Hald, Galbo et al 2011).…”
Section: Definitive Endoderm Progenitorsmentioning
confidence: 98%